Surface roughness variance on different levels of surface inclination of powder bed fused tool steel 1.2709 - Karlsson Jussi; Piiroinen Aki; Korpela Markus; Salminen Antti (United Kingdom, 2022)
Evolution of additive manufacturing has allowed increased flexibility and complexity of designs over conventional manufacturing e.g. formative and subtractive manufacturing. Restricting factor of laser powder bed fusion of metals (PBF-LB/M) additive manufacturing is the as built surface quality. To promote an understanding of the surface roughness and suitable surface measuring technologies octagon shaped tool steel 1.2709 samples was developed and manufactured. Different surface measuring technologies was also literary reviewed. Studied samples were manufactured with commercially available laser-based powder bed fusion system using standard parameter set provided by the system manufacturer. Surface roughness was measured from top and down skins from multiple different building angles in a way that process specific effects, such as direction of movement of the powder re-coater, was considered. Based on these measuring results of the samples the effect surface inclination are discussed. The results show that building angle strongly affects to surface roughness of laser-based powder bed fused parts. Surface roughness was measured to be more than five times worse in unsupported angle manufactured down facing surfaces when compared with vertical walls.
18th Nordic Laser Materials Processing Conference (18th NOLAMP) 18th-20th January 2022, Luleå, Sweden